Perencanaan Geometri Jalan Hauling Batubara Dari ROM Pit Menuju ROM Port di PT. MNC Infratama Jobsite PT. Bhumi Sriwijaya Perdana Coal Provinsi Sumatera Selatan - Alfajriah Alfajriah; Tri Gamela Saldy (Journals Mining Engineering : Bina Tambang, 2023)
Every mining operation requires haul roads as a very important infrastructure facility. The purpose of this research is to plan a haul road and calculate the required road geometry design so that the Hino FM 260 JD dump truck can pass through it. Data collection methods used in this research are literature studies, observation, primary data and secondary data. The location to be studied has a road length of ± 11,2 km. The results of this study with planning a straight road width of 9 m while at a bend of 15 m, the minimum bend radius is 47 m with a turning radius of 8,5 m, the maximum superelevation obtained is 0.04, and a cross slope is obtained with a difference 18 cm high. The planned slope of the road is the maximum slope that can be passed properly by the conveyance. The slope would ideally be 8%. Based on the bend plan, there are 10 bend radii consisting of 5 SCS bends, 1 FC bend and 4 SS bends. In order to support the smoothness and safety of transportation activities, especially on hauling roads, it is necessary to take into account the road supporting factors to achieve these conditions, namely stopping distances and safety berms. On each left and right side of the road a safety embankment will be made with a width of 1.44 m with a height of 0.48 m and a safe/stopping distance for vehicles that is 41.463 m. The load received by the road surface is 16.000 lb/ft2. Therefore, a hauling road pavement is required with the addition of a cover layer with a material carrying capacity of 20.000 lb/ft2 Compact gravel and boulder-gravel formation; very compact sandy gravel.